Analysis of Teachers' Perceptions of Digital Education Policy in Civics Education Learning - Dewi, Ressi Kartika; Karsidi, Ravik (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2025)
In the context of digital development, digital education policy requires synergy between individuals and institutions. The Indonesian government has implemented various policies to promote digital transformation within the education system, aiming to improve the quality of civics education, expand access to education, and foster the development of good citizenship. Teachers’ perceptions of digital education policy are a key factor in determining the effectiveness of policy implementation in the classroom. This study aims to analyze teachers’ perceptions of digital education policy in civics educations learning, using a qualitative descriptive approach with a case study method. Data were collected through interviews and a teacher perception questionnaire adapted from cognitive theory. The validity of the data was tested using technique and source triangulation. The findings show that teachers generally have a positive view of digital education policy. They believe that internal student factors and the diversity of digital media influence learning success. However, 50% of teachers have not yet implemented digital media across all civics education materials. This indicates a need for greater convergence between education policy development and the practice of technology-based civics education learning in the classroom.